CONHECIMENTO DE GESTANTES SOBRE DIREITOS NO PRÉ-NATAL E PARTO E PUERPÉRIO PELO SUS: UMA REVISÃO INTEGRATIVA DE LITERATURA (CIPEEX, 2026)
Introduction: The SUS (Brazilian Unified Health System) guarantees pregnant women essential rights during prenatal care, childbirth, and the postpartum period, such as consultations, exams, and humanized childbirth. However, the lack of information undermines its effectiveness. This study analyzed the scientific literature on pregnant women’s knowledge regarding these rights and the difficulties in accessing them. Objective: The general objective of this study was to analyze what the scientific literature reveals about pregnant women’s knowledge of their rights ensured by SUS, focusing on prenatal care, childbirth, and the postpartum period, and identifying the main difficulties and challenges women face in accessing this information. Methodology: Five articles (2020–2025) were selected from the SciELO, PubMed, and CAPES databases. The results indicated limited knowledge, especially regarding autonomy in childbirth, analgesia, and family planning, although consultations and exams were better understood. Results: Misinformation was associated with insufficient communication from professionals and weaknesses in educational policies. The studies emphasized the need to train health teams and implement more effective dissemination strategies, thus expanding pregnant women’s autonomy. Conclusion: It is concluded that strengthening health education during prenatal care is crucial to ensure the full exercise of rights, despite the study’s limitations, such as the small number of articles and the restricted time frame. Future research should evaluate educational interventions and expand data sources.
Keywords: Direitos das gestantes; Pré-natal; Parto; Puerpério; Sistema único de Saúde